Respuesta :
Answer:
136
Step-by-step explanation:
This is an arithmetic sequence
The formula is an = a1 + f × (n-1)
n= the number we are trying to find = 37
a= the number in any given space on the sequence
a1= 460
f= the common difference between the numbers
f= -9 because you subtract 9 from each to get the number
a37= 460-9(37-1)
a37= 460-9(36)
a37= 460- 324
a37= 136
Given :
[tex] \\ [/tex]
- The first three terms of a sequence are 460, 451, 442
[tex] \\ [/tex]
To Find :
[tex] \\ [/tex]
- 37th term of sequence = ?
[tex] \\ [/tex]
Solution :
[tex] \\ [/tex]
Clearly these three terms are making an arithmetic sequence, with :
- First term, a = 460
- Common difference, d = 451 - 460 = - 9
[tex] \\ [/tex]
Now, we have to find 37th term of sequence = [tex] \tt a_{37}[/tex]
[tex] \\ [/tex]
Now, we know that :
[tex] \large \underline{\boxed{\bf{a_{n} = a + (n-1)d}}}[/tex]
[tex] \\ [/tex]
[tex] \tt : \implies a_{37} = a + (37-1)d[/tex]
[tex] \tt : \implies a_{37} = a + 36d[/tex]
[tex] \\ [/tex]
Now, by substituting values of a and d :
[tex] \tt : \implies a_{37} = 460 + 36 \times (-9)[/tex]
[tex] \tt : \implies a_{37} = 460 - 324[/tex]
[tex] \tt : \implies a_{37} = 136[/tex]
[tex] \\ [/tex]
Hence, value of 37th term of given sequence is 136.